Experimental Gonococcal Infection in Male Volunteers: Cumulative Experience with Neisseria gonorrhoeae Strains FA1090 and MS11mkC - Hobbs, Marcia M.; Sparling, Philip F.; Cohen, Myron S.; Shafer, William M.; Deal, Carolyn D.; Jerse, Ann E. (Frontiers in Microbiology, 2011)
Experimental infection of male volunteers with Neisseria gonorrhoeae is safe and reproduces the clinical features of naturally acquired gonococcal urethritis. Human inoculation studies have helped define the natural history of experimental infection with two well-characterized strains of N. gonorrhoeae, FA1090 and MS11mkC. The human model has proved useful for testing the importance of putative gonococcal virulence factors for urethral infection in men. Studies with isogenic mutants have improved our understanding of the requirements for gonococcal LOS structures, pili, opacity proteins, IgA1 protease and the ability of infecting organisms to obtain iron from human transferrin and lactoferrin during uncomplicated urethritis. The model also presents opportunities to examine innate host immune responses that may be exploited or improved in development and testing of gonococcal vaccines. Here we review results to date with human experimental gonorrhea.